Banking permits: Economic efficiency and distributional effects - Valentina Bosetti; Carlo Carraro; Emanuele Massetti (Fondazione Eni Enrico Mattei (FEEM), 2008)
Most analyses of the Kyoto flexibility mechanisms focus on the cost effectiveness of 'where' flexibility (e.g. by showing that mitigation costs are lower in a global permit market than in regional markets or in permit markets confined to Annex 1 countries). Less attention has been devoted to 'when' flexibility, i.e. to the benefits of allowing emission permit traders to bank their permits for future use. In the model presented in this paper, banking of carbon allowances in a global permit market is fully endogenised, i.e. agents may decide to bank permits by taking into account their present and future needs and the present and future decisions of all the other agents. It is therefore possible to identify under what conditions traders find it optimal to bank permits, when banking is socially optimal, and what are the implications for present and future permit prices. We can also explain why the equilibrium rate of growth of permit prices is likely to be larger than the equilibrium interest rate. Most importantly, this paper analyses the efficiency and distributional consequences of allowing markets to optimally allocate emission permits across regions and over time. The welfare and distributional effects of an optimal intertemporal emission trading scheme are assessed for different initial allocation rules. Finally, the impact of banking on carbon emissions, technological progress, and optimal investment decisions is quantified and the incentives that banking provides to accelerate technological innovation and diffusion are also discussed. Among the many results, we show that not only does banking reduce abatement costs, but it also increases the amount of GHG emissions abated in the short-term. It should therefore belong to all emission trading schemes under construction.
Keywords: C72; H23; Q25; Q28; 330; Emission Trading; Banking; Emissionshandel; Wirtschaftliche Effizienz; Verteilungswirkung; Allokationseffizienz; Energiemanagement; Investition; Regenerative Energie; Welt